Jenis Pajak dalam Pengelolaan Keuangan di SMA Negeri 13 Surabaya - Noer Adila Azzahra; Nur Azizah; Nadia Dewi Firdaus; Syunu Trihantoyo (Journal of International Multidisciplinary Research, 2024)
This study aims to determine the type of the taxes in school financial management. This study use basic qualitative or descriptive research approach with data collection techniques in this study are interviews and documentation. The data analysis use are data presentation and verification. The result of study obtained information about the type of taxes paid by SMA Negeri 13 Surabaya, namely Value Added Taxes and Income Taxes. At the SMA Negeri 13 Surabaya, transparency in the use of taxes in scholl is making accountability reports. The school treasure makes transparent accountability reports related to the use of tax funds in detail to interested parties. In order to comply with applicable tax regulatioms, SMAN 13 Surabaya several things, namely; [1] understand the applicable tax regulations in the school area; [2] identify relevant tax liabilities; [3] conduct tax planning to minimize the tax burden as much as legally possible; [4] register as taxpayer; [5] collect and make timely payment of taxes; [6] conduct tax reporting in accordance with applicable regulations.